Verification of sap flow characteristics and measurement errors of Populus tomentosa Carr. and Salix babylonica L. based on the liquid level equilibrium method - Liu, Yunjie; Zhang, Hanhan; Ma, Changming; Liu, Bingxiang; Ding, Changjun (Frontiers in Plant Science, 2022)
This study clarified the characteristics and influencing factors of sap flow in Populus tomentosa Carr. and Salix babylonica L., and verified the applicability of Granier’s original formula for measuring the sap flow of the two species, aimed to provide a basis for the accurate assessment of tree transpiration. P. tomentosa and S. babylonica were used as research objects, their sap flow was measured by the thermal dissipation probe method (TDP), together with changes in meteorological factors and soil water content. Meanwhile, the transpiration of both species was measured by the liquid level equilibrium method (LLE) to verify the applicability of Granier’s original formula. We found that: (1) the sap flow velocity of P. tomentosa and S. babylonica under typical sunny and cloudy conditions showed unimodal or bimodal changes, which were highly significantly correlated with meteorological factors (P < 0.01), but they were all small and poorly correlated with meteorological factors on rainy days. (2) The sap flow velocity of both species was significantly and negatively correlated (P < 0.05) with the daily change in stem and soil water content at 10–20 cm. (3) Compared to that calculated with the LLE method, the sap flows of the two species calculated by the TDP technique using Granier’s original formula were seriously underestimated, with error rates of -60.96% and -63.37%, respectively. The Granier’s correction formulas for P. tomentosa and S. babylonica established by the LLE method were Fd = 0.0287K1.236 (R2 = 0.941) and Fd = 0.0145K0.852 (R2 = 0.904), respectively, and the combined correction formula was Fd = 0.0235K1.080 (R2 = 0.957). It was verified that the errors of sap flow calculated by the specific correction formulas for P. tomentosa and S. babylonica were -6.18% and -5.86%, and those calculated by the combined correction formula were -12.76% and -2.32%, respectively. Therefore, the characteristics of the sap flow velocity of P. tomentosa and S. babylonica on sunny, cloudy and rainy days were different and significantly influenced by meteorological factors. The original Granier’s formula for calculating their sap flow resulted in a large error, but can be measured more accurately by constructing specific correction and combination formulas through the LLE method.